Brawling From the Perspective of Positive Criminal and Islamic Criminal - Aicha Azdina Adly Fesya; Khaidar Damanik (AT-TAFAHUM: Journal of Law, 2019)
Crime is an unlawful act that violates legal norms and may result in criminal sanctions, including violations of the human right to security as guaranteed by the 1945 Constitution of Indonesia. Criminal law functions to regulate prohibited acts and impose sanctions on perpetrators. From an Islamic perspective, the Qur’an emphasizes values of brotherhood, peace, justice, and prohibits conflicts or disputes without legitimate reasons. This study aims to analyze the resolution of brawls from the perspectives of positive law and Islamic law. The research employs a normative juridical method using a literature study approach by examining laws, regulations, legal doctrines, and Islamic legal sources related to juvenile delinquency and criminal acts involving brawls. The findings indicate that the handling of brawls, which generally involve children and adolescents, requires special protection in accordance with applicable laws and regulations. Such protection includes humane treatment, the provision of legal assistance, safeguarding children’s rights during legal proceedings, and avoiding excessive or severe punishment. In addition, restorative and preventive approaches are considered important in addressing juvenile involvement in brawls. The study also highlights that the effectiveness of resolving brawls is influenced by the role of law enforcement officers, family supervision, educational institutions, and public legal awareness. Therefore, collaboration among these parties is necessary to prevent and reduce the occurrence of brawls while promoting justice, protection, and social harmony.